2015
DOI: 10.17795/jjnpp-18396
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Hydro-Alcoholic Extract of Foeniculum vulgare Mill on Leukocytes and Hematological Tests in Male Rats

Abstract: Background:Medicinal plants have a long history in treating blood disorders, which is one of the most common problems in today's advanced world. Fennel (Foeniculum vulgare) is a medicinal plant with a high content of polyphenols and has antioxidant and immunomodulatory properties. Objectives: The aim of this study was to evaluate the effect of hydro-alcoholic extract of fennel on some hematological indices in male rats. Materials and Methods: In this experimental study, thirty male Wistar rats were divided int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 21 publications
2
24
0
Order By: Relevance
“…Aromatic property of Foeniculum vulgare is responsible for its utilization in cosmetic industry as well as food and beverages [14]. Though leaves and stalks of herb are consumed as vegetable, but seeds are considered as most useful [15].…”
Section: Introductionmentioning
confidence: 99%
“…Aromatic property of Foeniculum vulgare is responsible for its utilization in cosmetic industry as well as food and beverages [14]. Though leaves and stalks of herb are consumed as vegetable, but seeds are considered as most useful [15].…”
Section: Introductionmentioning
confidence: 99%
“…The herb is an aromatic plant belonging to the Umbelliferae family, and is an annual, biennial, or perennial plant about 2.5 m in height with feathery leaves and yellow flowers (19) and indigenous to the shores of the Mediterranean and southern Europe (2). The usable parts of the fennel plant are the root, leaf, and fruit (23). Its therapeutic properties are due to volatile compounds, phenols, and flavonoids in the plant extract.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship of lymphoid follicles in Bursa of Fabricius with antibody titers has also been proved by Qureshi et al [11], that bursa of Fabricius damage due to infection with infectious bursal disease virus caused depletion of lymphocytes in medulla lymphoid follicles and the fall of antibody titers in the blood of [12]. Other studies showed that extracts of alcohol fennel can increase the average red blood cells and white blood cells in the rat at a dose of 250 mg/kg and can increase cloting time (CT) at a dose of 500 mg/kg [13].…”
Section: Discussionmentioning
confidence: 91%
“…Type A is classified into several subtypes based on the surface antigens, i.e. 16 subtypes of HA (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16) and nine subtypes of NA (1-9) [5,6]. Type A of influenza is not only responsible for disease problem in birds, humans and pigs, but also the aquatic mamals, namely seals and whales [7].…”
mentioning
confidence: 99%